Storytelling: uma metodologia ativa para o ensino de matemática - Aprigio, Phellippe (2024)
In a society that should value attitudes of cooperation, collaboration, creativity and critical thinking more, it is necessary to rethink educational practices and research possibilities for how to better teach in the classroom. In this context, active methodologies stand out, with which we seek to promote the protagonism of students in their teaching and learning process. Thus, this research proposes the use of an active methodology for teaching Mathematics: Storytelling; a term that can be literally translated as narrative or storytelling. However, the concept of Storytelling is broader, because it encompasses technical and artistic concepts and is used as a communication tool. Currently, Storytelling is widely used in advertising campaigns and in corporate sectors, and because it is an effective communication tool that establishes a relationship of empathy between the recipients of a message and the characters in the narratives, it is understood that it has great potential as a teaching methodology that is still unexplored. In this sense, this research aimed to investigate Storytelling as an active methodology for teaching Mathematics, as well as to present concepts inherent to it, researching its possible potentialities, in addition to conducting a teacher training course in order to promote its use in pedagogical planning. The objectives were summarized in the following question: How can teachers use Storytelling in Mathematics classes? To this end, an applied research was conducted with a qualitative approach, of an exploratory nature and with methodological procedures of Action Research, implementing an extension course for continued training of Basic Education teachers, exploring possibilities for Storytelling in Mathematics classes. During the course, data were produced through the application of two questionnaires and the use of a field diary. These data were examined according to Interpretative Analysis. The results showed that Storytelling can be considered an efficient, innovative and differentiated active methodology for teaching this subject and Mathematics Education, having many potentialities, such as the ability to promote protagonism and engagement of students and teachers, as well as the presentation and learning of content in a more interesting, attractive and engaging way.